Predation, Efficiency, and Inequality - Herschel I. Grossman; Minseong Kim (Brown University, Department of Economics, 2002)
This paper analyzes a general-equilibrium model in which each person can choose to be either a producer or a predator. This model shows how predation breaks the link between the interpersonal distribution of productive resources and the interpersonal distribution of consumption. SpeciÞcally, we Þnd that in this model the Rawlsian criterion of maximizing the expected consumption of the least advantaged person selects an unegalitarian distribution of productive resources in which a positive fraction of people have only the minimum possible endowment of productive resources. Also, an egalitarian distribution of productive resources is not even Pareto efficient.
Keywords: D31; D50; D60; D74; 330